The changing landscape of semiconductor manufacturing: why the health sector should care - Zhai, Kevin (Frontiers in Health Services, 2023)
As semiconductor devices become increasingly ubiquitous in healthcare, the health sector has in turn grown highly dependent on the semiconductor industry. This relationship is not always symbiotic, and even mild turbulence in the semiconductor industry has the potential to derail patient care. Here, we introduce semiconductor manufacturing and discuss political and economic forces that will shape the industry for years to come. The uncertain outlook for semiconductors underscores the need for stakeholder collaboration to ensure an adequate supply of semiconductor-utilizing medical devices for the patients of today and tomorrow.